1981
DOI: 10.2134/agronj1981.00021962007300010016x
|View full text |Cite
|
Sign up to set email alerts
|

Hay Yield Determinations of Mixed Swards Using a Disk Meter1

Abstract: Estimates of hay yields are frequently desirable for purposes of measuring fertilizer response, studying effects of management and cultural practices, and determining animal units that can be maintained on forage produced from a given area. Estimates of forage yield can be obtained by cutting and weighing, but the random collection of forage samples for estimating yields is not a viable alternative in some cases. A convenient, quick, and accurate method of determining forage yields in situ would benefit resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
8
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…1991. S and L were similarly well correlated with DM.DiscussionThe scatter of calibration data(Figure 1)shows a curvilinear trend similar to that reported byEarle and McGowan (1979) andBaker et al (1981). The curve was most pronounced between S values of 150 and 200 mm.…”
supporting
confidence: 86%
“…1991. S and L were similarly well correlated with DM.DiscussionThe scatter of calibration data(Figure 1)shows a curvilinear trend similar to that reported byEarle and McGowan (1979) andBaker et al (1981). The curve was most pronounced between S values of 150 and 200 mm.…”
supporting
confidence: 86%
“…1962) to&borate mechanismswhichemploycounters and gears to automatically determine and record the resting height ofametal plate (Earleand McGowan 1979). Most numerous ofall, however, are "disc meters" employing circular plates constructed from wood (Baker et al 1981) or metal (Castle 1976, Powell 1974, Santillan et al 1979). These devices, while generally useful to determine forage bulk.…”
mentioning
confidence: 99%
“…BRANS-BY et al (1977) recommended frequent calibration throughout the season for pasture. BAKER et al (1981), however, found no difference in the slope of the regression line between DMH and DM due to either species composition or growth stage for hay crops. The intercept was, however, different for different growth stages.…”
Section: Introductionmentioning
confidence: 74%
“…There is no agreement in the literature concerning the effect of plant species, growth stage, botanical composition, etc., on the relationship benveen DMH and DM (BAKER et al 1981, BRANSBY et al 1977, LOPEZ 1980. BRANS-BY et al (1977) recommended frequent calibration throughout the season for pasture.…”
Section: Introductionmentioning
confidence: 99%